2013
DOI: 10.1039/c2dt32203j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between inorganic pigments and proteinaceous binders in reference paint reconstructions

Abstract: The degradation of the proteinaceous binders, ovalbumin (OVA) and casein, and their interactions with azurite (Cu(3)(CO(3))(2)(OH)(2)), calcium carbonate (CaCO(3)), hematite (Fe(2)O(3)) and red lead (Pb(3)O(4)) pigments were studied. A multi-analytical approach based on Thermogravimetric Analysis (TG), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR) and Size Exclusion Chromatography (SEC) was used. The research was carried out on a set of paint reconstructions, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 52 publications
(68 reference statements)
6
63
0
Order By: Relevance
“…On the other hand, it is reported that medium-rich proteinaceous red lead paints are stable to light, the binder protecting the pigment [239]. Moreover, the pigmented layer has different properties than an unpigmented one [51]. It is soluble in diluted acids (nitric, chloridric, oxalic, acetic), with formation of the corresponding salts, and when heated it transforms to litharge [1,240].…”
Section: Red Lead (Pb 3 O 4 )mentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it is reported that medium-rich proteinaceous red lead paints are stable to light, the binder protecting the pigment [239]. Moreover, the pigmented layer has different properties than an unpigmented one [51]. It is soluble in diluted acids (nitric, chloridric, oxalic, acetic), with formation of the corresponding salts, and when heated it transforms to litharge [1,240].…”
Section: Red Lead (Pb 3 O 4 )mentioning
confidence: 99%
“…In oil layers, Fe-ions promote photo-oxidative reactions, while Mn-ions act as a siccative [12]. In proteinaceous binder, interactions are reported between pigment and medium [51]. In rabbit skin glue, haematite shows a high degree of interaction with the binder, making the paint layer more stable than for other pigments [65].…”
Section: Chalk Pigments [(Camg)co 3 : Natural/artificial Lime Whitementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, hydrolysis of triglycerides, which results in the release of long and short chain fatty acids and diacids as well as formation of cross-linked aggregates including cobalt-lecithin complexes has been reported (Mallégol et al, 2000). More recently, Duce et al have considered the ageing behavior of casein and ovoalbumin proteins in presence of cinnabar calcite, azurite, hematite and red lead (Duce et al, 2013) identifying alteration processes among which are induced aggregation of proteins by covalent cross-linking, oxidation of amino acids side chain and hydrolysis of the polypeptide chain in both pure and pigmented protein samples.…”
Section: E) Pigment-binder Interactionsmentioning
confidence: 99%